Frequency of walking physical exercise reduces blood sugar levels in diabetic - Lestari, Diana Tri; Rahmasari, Lutfir Fitri; Karyati, Sri; Jauhar, Muhamad (University of Muhammadiyah Semarang, 2024)
Diabetes mellitus is a global public health threat characterized by increasing morbidity and mortality rates. An unhealthy lifestyle causes this and has an impact on various kinds of disease complications and even death. One of the complementary interventions that can be carried out is physical exercise on foot. The research aimed to analyze the effect of physical walking exercise on blood sugar levels. Pre and post-test quasi-experimental research design without a control group. The study was conducted in January-February 2024 in the Ngembalrejo Community Health Center Working Area, Kudus Regency. The sample was 20 clients for each of the two intervention groups. Inclusion criteria were diagnosed diabetes mellitus, age 20-59 years, following all interventions, and no complications. Intervention group 1 did physical exercise three times a week, and intervention group 2 did physical exercise walking every day. The research instrument used an observation sheet and a glucometer—data analysis using paired t-tests and independent t-tests. The study's results showed a significant effect of physical walking exercise on blood sugar levels with a value of p=0.000 (p<0.05). Physical walking exercises can be carried out regularly by Diabetics, either independently or integrated with chronic disease management programs (PROLANIS), non-communicable disease patients, and elderly patients.